2019
DOI: 10.3390/v11040354
|View full text |Cite
|
Sign up to set email alerts
|

Description of a Natural Infection with Decapod Iridescent Virus 1 in Farmed Giant Freshwater Prawn, Macrobrachium rosenbergii

Abstract: Macrobrachium rosenbergii is a valuable freshwater prawn in Asian aquaculture. In recent years, a new symptom that was generally called “white head” has caused high mortality in M. rosenbergii farms in China. Samples of M. rosenbergii, M. nipponense, Procambarus clarkii, M. superbum, Penaeus vannamei, and Cladocera from a farm suffering from white head in Jiangsu Province were collected and analyzed in this study. Pathogen detection showed that all samples were positive for Decapod iridescent virus 1 (DIV1). H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 28 publications
2
79
0
Order By: Relevance
“…For the natural infection pathway, positive detections of DIV1 by PCR or qPCR have been reported in different natural samples of crustacean, including P. vannamei [9], P. chinensis [9], M. rosenbergii [9,23], C. quadricarinatus [8], Procambarus clarkii [23,24], P. japonicus [23], M. nipponense [23,24], M. superbum [24], and Cladocera [24]. Severe disease with high mortality has been reported and infection with DIV1 has been demonstrated in C. quadricarinatus , P. vannamei , and M. rosenbergii [8,9,24]. All of these have been confirmed as being susceptible species for DIV1, fulfilling the natural infection criteria of OIE standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the natural infection pathway, positive detections of DIV1 by PCR or qPCR have been reported in different natural samples of crustacean, including P. vannamei [9], P. chinensis [9], M. rosenbergii [9,23], C. quadricarinatus [8], Procambarus clarkii [23,24], P. japonicus [23], M. nipponense [23,24], M. superbum [24], and Cladocera [24]. Severe disease with high mortality has been reported and infection with DIV1 has been demonstrated in C. quadricarinatus , P. vannamei , and M. rosenbergii [8,9,24]. All of these have been confirmed as being susceptible species for DIV1, fulfilling the natural infection criteria of OIE standards.…”
Section: Discussionmentioning
confidence: 99%
“…All of these have been confirmed as being susceptible species for DIV1, fulfilling the natural infection criteria of OIE standards. The susceptibility of P. chinensis , P. japonicus , and M. superbum to DIV1 were not fully confirmed, as the evidence of PCR or qPCR positives [23,24] only supports the existence of DIV1. Confirmation of infection with DIV1 can usually be supported by evidence from histopathological evaluations, TEM, or in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the histopathological study using transmission electron microscopy of ultrathin sections and in situ hybridization indicated that SHIV mainly infects the hematopoietic tissue and hemocytes in the Pacific white shrimp ( 6 ). In 2019, the Executive Committee of the International Committee on Taxonomy of Viruses (ICTV) identified two virus isolates, SHIV and CQIV, as decapod iridescent virus 1 (DIV1) ( 10 ). Crustaceans in the coastal region of China, including L. vannamei, Fenneropenaeus chinensis, Exopalaemon carinicauda , and Macrobrachium rosenbergii , can all carry DIV1 ( 6 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The viruses have caused devastation in the prawn hatchery industries of Thailand [ 11 ], China [ 10 ], India [ 12 ], Taiwan [ 13 ] and Indonesia [ 14 ]. Other viruses causing mortalities include Macrobrachium rosenbergii Taihu Virus (MrTV), a novel dicistrovirus associated with larval mortalities in China [ 15 ], Infectious Hypodermal and Haematopoietic Necrosis Virus (IHHNV) [ 16 ], and Decapod Iridescent Virus (DIV1) [ 17 ]. Other pathogens have been identified to infect M. rosenbergii without large mortalities including: Macrobrachium Parvo-like Virus (MPV) [ 18 ] and White Spot Syndrome Virus (WSSV) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%